ANALISIS LAJU PERTUMBUHAN, EFEKTIVITAS, KONTRIBUSI PAJAK HOTEL DAN PAJAK RESTORAN DALAM PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) DI KOTA METRO - Elli Fitriyani; Nedi Hendri; Karnila Ali (FIDUSIA : JURNAL KEUANGAN DAN PERBANKAN, 2021)
The Indonesian government enforces a regional autonomy policy with the aim of making it easier for local governments to regulate their regional affairs independently. Metro City is one of the regions that implements its regional policy. One of the biggest potentials that Metro City has in financing regional expenditures comes from local taxes which are expected to be able to provide the largest contribution to Regional Original Revenue.This study aims to determine the rate of growth, the level of effectiveness of hotel and restaurant taxes and their contribution to local revenue in Metro City. This research uses a descriptive qualitative approach. Data obtained by conducting interviews, literature review and documentation. The data analysis technique uses growth rate analysis, effectiveness analysis, and contribution analysis. Based on the research results, the average hotel tax growth rate from 2016-2020 is said to be unsuccessful, while for restaurant tax it is said to be less successful. The average hotel and restaurant tax effectiveness in 2016-2020 with very effective criteria, and for the average level of hotel and restaurant tax contribution to PAD from 2016-2020 with very less contributing criteria.Keywords: Hotel Tax, Restaurant Tax, Regional Original Revenue.